Ethanol recovery from dilute aqueous solution by perstraction using supported ionic liquid membrane (SILM) - Huang, Ting-Yi (2021)
The recovery of ethanol from dilute aqueous solution by supported ionic liquid membrane (SILM) perstraction was investigated using three potential extracting solvent of trihexyl(tetradecyl)phosphonium ionic liquids (THTDP IL): [THTDP][Br], [THTDP][N(CN)2] and [THTDP][Tf2N], and three potential polymeric microporous membranes: polyvinylidene fluoride (PVDF) (hydrophilic Durapore® GVWP and hydrophobic Durapore® GVHP) and polypropylene (PP). The solvent was chosen based on hydrophobicity, thermal stability and negligible vapor pressure; while the membrane was chosen based on physicochemical properties, commercial availability and affordability. The optimized combination of solvent and membrane was assessed in a perstraction system. The [THTDP][N(CN)2]-GVHP SILM gave the best overall performance in terms of extraction and stability. At a feed concentration of 2 wt% ethanol, the selected SILM was able to maintain its functionality for ∼240 h without observable phase intermixing. Despite being subjected to constant lateral shear on the aqueous side, the SILM retained its integrity by maintaining a high ethanol flux of > 2.2 kg/m2·h (vs. ∼10-4 – 10-1 kg/m2·h in pervaporation) and selectivity of > 320 (vs. ∼20 in liquid-liquid extraction). Subsequently, the extracted ethanol was recovered from IL by single-stage vacuum-distillation with a final purity of 80% (vs. ∼20% in single-stage vacuum-distillation alone) and an overall selectivity of 200. The long-term stability, high flux and superior selectivity of the SILM perstraction system makes it a promising alternative to other energy intensive purification techniques such as distillation for the extraction of dilute ethanol as low as 2 wt% from fermentation broths.